Resistance of Micro, Small, and Medium Enterprise Owners to Halal Labeling Policy within Islamic Law Framework - Asnaini, Asnaini; Irwan Abdullah; Miko Polindi; Ahmad Muzakky; Ayu Yuningsih (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2025)
This study analyzes how resistance to halal labeling policies among Micro, Small, and Medium Enterprises (MSME) owners has influenced the experiences and challenges in educating about and implementing halal food policies in Indonesia, and even globally, particularly among food and beverage providers serving daily meals to the public. The MSME owner respondents interviewed for this study have been operating their businesses for a relatively long time and have been selling food and beverages without a halal label. A questionnaire was used to collect data on the reasons for rejection and its prevalence. Semi-structured interviews were conducted to explore key topics within thematic narratives. The research found that MSME owners’ resistance to halal labeling occurred covertly. This resistance stemmed from the miscommunication of the halal labeling policy and the differing understanding of halal standards among MSME owners, religious perspectives, and government regulations. Objections to the complex procedures and costs involved were also significant factors contributing to this resistance. MSME owners have not yet recognized the benefits of halal labeling for business growth and innovation, and instead, focus primarily on the immediate survival of their businesses to meet daily needs. MSMEs need assistance from other parties to advance and innovate. The resistance and contestation of halal values in MSMEs could potentially lead to violations of the principles of Islamic law, particularly in production and consumption.